Solvent-free synthesis of zeolite catalysts - Meng, Xiangju; Wu, Qinming; Chen, Fang; Xiao, Feng-Shou (Science China. Chemistry, 2015)
The most used method for preparation of zeolites is hydrothermal synthesis from silicate or aluminosilicate gels at temperatures in the range of 60-200 ℃. Excess water used in the industrial process results in several issues, including high autogeneous pressure, low efficiency, pollution, etc. To solve these problems, several strategies have been developed. This review describes the solvent-free synthesis of zeolites. The combination of solvent-free synthesis and organotemplate-free synthesis can open the pathway to a highly sustainable zeolite synthesis protocol in industry.